Child Marriage in Malaysia and Indonesia in Legal Anthropology Perspective: Between Local Traditions and Islamic Legal Regulation - Wahyudi Wahyudi; Muhammad Husni Abdulah Pakarti; Oyo Sunaryo Mukhlas; Beni Ahmad Saebeni; Mohd Radhuan Arif Zakaria (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
Child marriage remains a crucial issue in Indonesia and Malaysia even though both countries have laws restricting it. This study aims to analyze the dynamics of child marriage in the perspective of legal anthropology, focusing on the interaction between local traditions and Islamic legal regulations. Through a qualitative approach and literature study, this study found that the root of the problem of child marriage lies not only in economic and educational factors, but also in the strong influence of old-fashioned social, cultural, and religious norms that are often dialectic with formal law. In Indonesia, the existence of Law No. 16 of 2019 has not been fully effective due to the high number of marriage dispensation applications and the strong practice of elopement such as merariq. In Malaysia, state autonomy in Islamic family law creates regulatory variations and complexities in handling child marriage. This study concludes that a holistic approach through strengthening the role of religious courts, economic empowerment, inclusive education, and campaigns involving religious and customary leaders are key in breaking the chain of child marriage.